On the systematic position of the genus Timmiella (Dicranidae, Bryopsida) and its allied genera, with the description of a new family Timmiellaceae - Inoue, Yuya; Tsubota, Hiromi (Phytotaxa, 2014)
Based on our molecular phylogenetic analysis of haplolepideous mosses with concatenated sequences of chloroplast rps4 and rbcL genes, a new family Timmiellaceae is erected to accommodate the genera Timmiella and Luisierella, both of which have been formerly included in the family Pottiaceae. The family Timmiellaceae is resolved as a second-branching clade together with Distichium (Distichiaceae) within the Dicranidae (haplolepideous moss) lineages and phylogenetically distinct from the Pottiaceae. Reassessment of morphological characters suggests that a combination of the characters: 1) adaxially bulging and abaxially flat leaf surfaces, 2) sinistrorse or straight peristomes, when present, and 3) sinistrorsely arranged operculum cells is unique to Timmiellaceae and discriminates it from other haplolepideous moss families.